Kidney health for all: caring for people, protecting the planet - Vanholder, Raymond; Abdellatif, Dina; dos Santos Jr, Augusto Cesar Soares; Correa-Rotter, Ricardo; Gopalakrishnan, Natarajan; Wang, Bill; Roumeliotis, Stefanos; Balducci, Alessandro; Haris, Ágnes; Yadla, Manjusha; et al. (African Journal of Nephrology, 2026)
The current kidney care model - focused on late-stage disease and in-centre haemodialysis - is unsustainable, because of costs, environmental burden, poor outcomes, and reduced quality of life. The 78th World Health Assembly’s recognition of kidney disease as a serious health threat presents a critical opportunity to reshape kidney care. Aligned with this, the 2026 World Kidney Day theme, “Kidney Health for All: Caring for People, Protecting the Planet”, calls for a systematic change. A sustainable model must prioritise early detection and prevention, reducing the need for kidney replacement therapy. Transplantation and home dialysis benefit people with kidney failure, environment and society. Dialysis itself must become more ecofriendly without compromising care quality, recognising that planetary perturbations in turn affect kidney health. Conservative care should also be considered, particularly for elderly and frail patients, if the quality-of-life benefits outweigh the perspectives offered by dialysis. Achieving this shift requires coordinated action across all stakeholders; education and engagement of the public, policy makers and health professionals to raise awareness about the threat of kidney disease; and an urgent move toward patient-centred care.